Vasyl’ Pavlovych Pylypenko - HMEI of Ukraine "UMSA", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article deals with the 75th anniversary of the birthday of Honoured Doctor of Ukraine candidate of medical science associate professor of Higher medical educational institution of Ukraine «Ukrainian medical stomatological academy» Pylypenko V. P.